Applicability of modern technologies to Wrocław University Library maps processing and digitization - Osowska, Anna (Biblioteka Uniwersytecka we Wrocławiu, 2015)
Wrocław University Library computerization, which started in 1994, opened new perspectives in the field of library processes facilitation, mainly in processing and collection circulation. Maps Department underwent computerization relatively late but upon understanding the advantages of possessing a complete database collection and possibilities offered by digital media attempts have been made without any delay to reduce the backlog. The article presents the characteristics of modern technologies and tools used in the Department's everyday work, with special attention paid to collection processing and accessibility of digitized versions of cartographic documents.
Keywords: cartographic resources; MARC 21 format; computer catalogs; map cataloging; cartographic resources digitization; map processing